Effects of Estrogen Replacement Therapy with Vitamin E on Oxidative Stress in Hepatic and Pancreatic Tissues of Ovariectomized Diabetic Rats - Cay, Mehmet; Ulas, Mustafa (Medwell Online, 2010)
We investigate the effects of 17 beta-estradiol (E-2) and vitamin E on oxidative stress of hepatic and pancreatic tissues in Ovariectomized (OVX) diabetic rats. Fortynine rats were equally divided into seven groups: Control; OVX; OVX+E-2; OVX+E-2+Vitamin E; OVX+Diabetic; OVX+Diabetic+E-2 and OVX+Diabetic+E-2+Vitamin E. The Glutathione Peroxidase (GSH-Px), Superoxide Dismutase (SOD), Catalase (CAT), Glutathione (GSH) and vitamin A and beta-carotene in liver and pancreas were reduced when compared with control but Malondialdehide (MDA) was raised. E-2 and E-2+vitamin E supplementations to OVX rats increased GSH-Px, SOD, CAT, GSH, vitamin A and beta-carotene in liver and pancreas but decreased MDA. MDA in liver and pancreas, Aspartate amino Transferase (AST), Alanine amino Transferase (ALT), Lactate Dehydrogenase (LDH), beta-glutamyl Transferase (GGT) and Alkaline Phosphatase (ALP) in the serum of diabetic OVX rats were raised when compared with OVX but the activities antioxidant enzyme, GSH, vitamin A and beta-carotene in liver and pancreas were lowered. The GSH-Px, SOD, CAT, GSH, vitamin A and beta-carotene in liver and pancreas increased, although MDA in liver and pancreas and AST, ALT, LDH, GUT and ALP in serum decreased in diabetic OVX after E-2 and E-2+vitamin E supplementation.
Keywords: Ovariectomy; estrogen; vitamin E; MDA; AST; ALT